Secret life an adaptation of a story by Jeff VanderMeer - Ellsworth, Theo; VanderMeer, Jeff 1968- (Drawn and Quarterly, 2021)
"At the centre of Secret Life is The Building, an office building wherein several factions vie for dominance... Jeff VanderMeer's ecological speculations overlap with Theo Ellsworth's deep-layered style to create a mind-bending narrative that defamiliarizes the mundanity of office work and makes the arcane rituals of The Building home... Secret Life observes the sinister individualism of bureaucratic settings in contrast with an unconcerned natural world. As the narrative progresses you may begin to suspect that the world Ellsworth has brought to life with hypnotic visuals is not so secret after all; in fact, it's uncannily similar to our own."--
Graphic novel adaptation of Secret Life by Jeff VanderMeer, published 2004 by Golden Gryphon Press
Keywords: Bürohaus; Büroarbeit; Geheimnis; Natur; Comic